2016
DOI: 10.1177/0042098016664299
|View full text |Cite
|
Sign up to set email alerts
|

Place-based correlates of Motor Vehicle Theft and Recovery: Measuring spatial influence across neighbourhood context

Abstract: Social scientists have long shown great interest in the spatial correlates of crime patterns. A subset of the literature has focused on how micro-level spatial factors influence the formation of crime hot spots. At the same time, tangential research has highlighted how neighbourhood disadvantage influences crime occurrence. The current study focuses on the intersection of these perspectives through a spatial analysis of Motor Vehicle Theft (MVT) and Motor Vehicle Recovery (MVR) in Colorado Springs, CO. We begi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
8

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 68 publications
1
26
0
8
Order By: Relevance
“…Piza et al (2016) for instance noted that while there are city wide risk factors there is also significant variation between different types of neighborhoods in their impact. For instance it was noted that the association of a park with motor vehicle theft was seven times greater in neighborhoods with a high share of young males in the population ).…”
Section: Risk Terrain Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…Piza et al (2016) for instance noted that while there are city wide risk factors there is also significant variation between different types of neighborhoods in their impact. For instance it was noted that the association of a park with motor vehicle theft was seven times greater in neighborhoods with a high share of young males in the population ).…”
Section: Risk Terrain Modelingmentioning
confidence: 99%
“…In addition it builds on the findings of Piza et al (2016) and Ceccato et al (2013) that suggested potential benefits from including the neighborhood level variable of collective efficacy, by employing mixed effects models of bus stops nested in neighborhoods with concentrated disadvantage and collective efficacy as neighborhood level variables. As the bus stop data was only available for a full year it was however not possible to include near repeat patterning or similarly dynamic models into the present study.…”
Section: Risk Terrain Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Vehicle Theft data for Taoyuan City was sourced from an open data platform (Open Data Platform of Taiwan: https://data.gov.tw). We chose the Vehicle Theft to be our prediction target because it is obviously affected by environment factors [35]. We used a data period from January 2015 to April 2018, with about 220 criminal incidents occurring each month.…”
Section: Data and Analysis Toolsmentioning
confidence: 99%
“…The costs of vehicle theft include the direct uninsured financial losses, the opportunity cost of the time taken to deal with the crime, the opportunity cost of the temporary unavailability of a vehicle, and the psychological costs of victimization [3][4][5]. Although the amount of vehicle theft and other crimes greatly decreased in the past few decades in many countries [6,7], vehicle theft still substantially contributes to crime statistics [8][9][10][11][12]. Most studies on vehicle theft were conducted in developed countries, though many developing countries suffer from growing rates of such crime.…”
Section: Introductionmentioning
confidence: 99%